Plan S and Open Access (OA) in Quebec: What Does the Revised FRQ OA Policy Mean for Researchers? - Harris, Rachel; Lange, Jessica; Lasou, Pierre (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2024)
Objective – Our article examines the effects of Quebec’s provincial funding agency (FRQ)’s revised 2022 OA policy on researchers. Following FRQ’s participation as a cOAlition S funding agency, which involves endorsing Plan S principles, we provide an overview of the OA options for researchers. We examine these options under the FRQ 2019 and FRQ 2022 policy years, account for the effect of transformative agreements (TA) on OA publishing options, as well as the financial implications for researchers under the revised policy.Methods – The researchers extracted a list of FRQ-funded publications from years 2020 to 2022 using the DOI registration agency Crossref. Using this sample set, the researchers quantitatively analyzed OA options under the previous policy and the revised one, comparing the two. To determine the effect of transformative agreements (TAs)s, we reviewed current agreements offered through Canada’s national licensing agency Canadian Research Knowledge Network (CRKN).Results – We found that the self-archiving method for open access (OA) is reduced under the revised 2022 policy. Our results lead us to anticipate the pressure felt by authors who will be required to pay article processing charges (APCs) to meet grant requirements.Conclusion – The current publishing patterns of FRQ-funded researchers are primarily concentrated in hybrid journals not covered by transformative agreements. As such, researchers will face additional financial costs should these publishing patterns continue. Concerted efforts among all stakeholders (researchers, universities, libraries, and funders) are needed to sustainably transition to immediate OA.